Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd004128.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia for neuroprotection in adults after cardiopulmonary resuscitation

Abstract: Conventional cooling methods to induce mild therapeutic hypothermia seem to improve survival and neurologic outcome after cardiac arrest. Our review supports the current best medical practice as recommended by the International Resuscitation Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 70 publications
4
130
4
4
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18] However, its effects on mortality and neurological outcome remain unclear, especially in patients who cannot receive DC. Therefore, we conducted a RCT to address this issue.…”
Section: February 2016mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18] However, its effects on mortality and neurological outcome remain unclear, especially in patients who cannot receive DC. Therefore, we conducted a RCT to address this issue.…”
Section: February 2016mentioning
confidence: 99%
“…However, the safety of mild hypothermia in patients with MCHI had been confirmed by many studies. [9][10][11][12][13][14][15][16][17][18] The complications associated with hypothermia included pneumonia, hyperglycemia, electrolyte disorders, and arrhythmia, among others. 39 However, no significant differences with normothermia treatment were recorded.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed a beneficial neurologic outcome of hypothermia closely related to its neuroprotective effect. It increased survival without major neurological sequelae for comatose patients after a CA following a ventricular fibrillation or tachycardia resuscitated successfully [6,7,11] . In this context, a protocol for cerebral protection by hypothermia after CA was introduced in the Intensive Care Unit (ICU) of Saint-Pierre University Hospital in 2004 and was updated regularly.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cooling or mild therapeutic hypothermia (MTH) is based on extensive laboratory evidence and clinical studies that highlight the beneficial effect of cooling to a core temperature of 33-34°C to secondarily mitigate brain damage, and hence to improve the neurological outcome [9][10][11].…”
mentioning
confidence: 99%